Activatable Multimodal Probes for In Vivo Imaging and Theranostics. Issue 50 (27th October 2022) - Wang, Yuqi; Hu, Yuxuan; Ye, Deju
Abstract: Multimodal imaging, which harnesses two or more imaging modalities to produce complementary anatomical and molecular information of a living subject, has become as a powerful tool in both basic biomedical research and clinical diagnosis. The progresses in multimodal imaging are paralleled by the advances in multimodal probes, particularly activatable multimodal imaging probes that can generate concurrent switches in different imaging modality signals upon interaction with a molecular target. These probes are extremely promising for in vivo imaging. In this Minireview, we summarize the recent progress in activatable multimodal probes for in vivo imaging and cancer theranostics, focusing on their design principle, signal activation mechanism and biomedical applications. The current challenges and perspectives for future developments of activatable multimodal probes are also briefly discussed. We hope that this Minireview will provide inspiration for the design of other activatable multimodal probes for improving in vivo imaging and theranostics. Abstract : Activatable probes capable of generating switchable multimodal imaging signals upon interaction with a molecular target of interest have attracted much attention in the past few years. This Minireview summarizes the recent progress in the development of activatable multimodal probes for in vivo imaging and theranostics, with a focus on their design, signal activation mechanism and biological applications.